ANALISIS WACANA NASKAH DRAMA “RUWET” KARYA SUNARDI: ANALISIS WACANA NASKAH DRAMA “RUWET” KARYA SUNARDI - Anastasia Septianggi Sri Hartanti; Ike Anisa Anisa (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
The Drama Script entitled “Ruwet” by Sunardi, M.Pd was analyzed in the study of grammatical and lexical discourse. Discourse analysis. The grammatical aspect consists of four parts, namely reference, insertion, duplication, and stringing. The lexical aspect is the relationship between the elements contained in the discourse. The lexical aspect consists of six parts, namely repetition, synonym, antonymy, collocation, and hyponymy. Researchers are interested in researching the drama script entitled "Ruwet" because the storyline is very interesting and the scenes written in the drama script entitled "Ruwet" are taken from real life. This drama is also interesting to research because it is a drama that has just been made and will be staged. The drama script entitled "Ruwet" also contains a lot of moral messages.